Perkembangan Teknologi Informasi, TFP, dan Emisi Gas CO2 di Indonesia - Moddilani, Ganiko; Irwandi, Irwandi (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
This paper examines the development of information technology, total factor productivity (TFP), and urbanization of CO2 gas emissions in Indonesia from 1975–2014. To discuss empirically, this study uses the Autoregressive Distributed Lag (ARDL) model. There are several results in this study. Firstly, the TFP coefficient value in the short term is lower than the long term, so that the Enviromental Kuznets Curve (EKC) hypothesis is not proven. This is one of the causes of rising CO2 gas emissions. Secondly, information technology has a significant impact on the increase of CO2 gas emissions. Thirdly, Indonesia’s urbanization has reduced CO2 gas emissions.